LITERASI KEUANGAN MAHASISWA DAN FAKTOR YANG MEMPENGARUHINYA - Ramadhan, ZUlfikar; Prakoso, Fajar Adi; Taufan, Januar; Hazizah, Zakiyah Nur; Irawan, Rinto (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
This research aims to determine students' financial literacy and the factors that influence it, namely pocket money, parental income, and parental education. The research sample was students from the Faculty of Economics and Business, Muhammadiyah University, Jakarta, who were taken randomly. Data were processed using multiple linear regression analysis. The research results show that pocket money and parental education have a positive and significant effect on the financial literacy of students at the Faculty of Economics and Business, Muhammadiyah University, Jakarta. Meanwhile, parental income has a positive and insignificant effect on the financial literacy of students at the Faculty of Economics and Business, Muhammadiyah University, Jakarta.Keywords: pocket money, parental income, parental education, financial literacy